Cyber Atmospherics and its Impact on E-Retailing Buyer Behavior : A Factor Analysis - Bhattacharya, Sourabh; Mishra, Bibhuti Bhusan (Prabandhan: Indian Journal of Management, 2016)
E-Commerce is booming in India. A number of industries are emphasizing on it to increase their sales. Fuelled by VC money, E-retailing companies are sacrificing profitability to acquire more consumers. Amazon has already emerged as a leader in terms of visitors followed by Flipkart and SnapDeal. E-retailers are creating superb conducive cyber atmospherics to attract more consumers. The present study attempted to assess the impact of cyber atmospherics on buyer behavior in terms of reliance, contentment, and adhesion. A survey on 300 individuals was conducted for this. Factor analysis on the survey generated interesting insights like emphasis of consumers on reasonable prices ; superb online ambience in terms of design, color, font, size; presence of options; and facilities for feedback sharing through social media. Factor analysis also found that importance is given by consumers to contentment in engaging with an electronic retailer in the long term. The results generated have immense managerial implications as a number of new domestic and international entrants are very eager to have complete knowledge of the pulse of Indian consumers.